2021
DOI: 10.3758/s13428-021-01633-2
|View full text |Cite
|
Sign up to set email alerts
|

Central tendency biases must be accounted for to consistently capture Bayesian cue combination in continuous response data

Abstract: Observers in perceptual tasks are often reported to combine multiple sensory cues in a weighted average that improves precision—in some studies, approaching statistically optimal (Bayesian) weighting, but in others departing from optimality, or not benefitting from combined cues at all. To correctly conclude which combination rules observers use, it is crucial to have accurate measures of their sensory precision and cue weighting. Here, we present a new approach for accurately recovering these parameters in pe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 21 publications
(37 citation statements)
references
References 50 publications
0
37
0
Order By: Relevance
“…In that paper, we also discussed the effects of additional response noise (e.g., motor noise). We showed that if the additional noise is equivalent across all trial types (single and combined cue trials), then it does not disrupt a researcher's ability to detect a reduction in variability using both cues compared to the best single-what we termed the "combination effect" (see equation 3 in Aston et al, 2022). However, the equivalence between the optimal prediction and measured variability using both cues (where the optimal prediction is calculated from the measured single cue variabilities) is not preserved.…”
Section: Limitationsmentioning
confidence: 97%
“…In that paper, we also discussed the effects of additional response noise (e.g., motor noise). We showed that if the additional noise is equivalent across all trial types (single and combined cue trials), then it does not disrupt a researcher's ability to detect a reduction in variability using both cues compared to the best single-what we termed the "combination effect" (see equation 3 in Aston et al, 2022). However, the equivalence between the optimal prediction and measured variability using both cues (where the optimal prediction is calculated from the measured single cue variabilities) is not preserved.…”
Section: Limitationsmentioning
confidence: 97%
“…To calculate matching variability we used a method described fully elsewhere (Aston, Negen, et al, 2021). In brief, the method is designed to account for central biases in continuous responses that may reduce statistical power for detecting a gain in precision using multiple cues.…”
Section: Discussionmentioning
confidence: 99%
“…The weight placed on the novel cue was calculated for each of the four types of conflict adjustment To calculate the weight placed on the novel cue we again used a method that is described fully elsewhere (Aston, Negen, et al, 2021). In brief, we model matches, 𝑚, as…”
Section: Discussionmentioning
confidence: 99%
“…Thus, our main measure of interest is precision or, equivalently, variability. We calculate measures of variability according to a method we recently described elsewhere (Aston, Negen, Nardini, & Beierholm, 2021). The method is designed to account for central biases in continuous responses that may reduce statistical power for detecting a gain in precision using multiple cues.…”
Section: Discussionmentioning
confidence: 99%